2011
DOI: 10.1260/1756-8277.3.4.273
|View full text |Cite
|
Sign up to set email alerts
|

Self-Exited Oscillation in a Combustion Chamber Driven by Phase Change in the Liquid Fuel Feed System

Abstract: A new mechanism for the generation of a self-exited oscillation of combustion in a generic combustion chamber typical for aeroengine combustors is described. The cause of the oscillation is the phase change from liquid to vapour which happens when the preheat temperature of the air flowing through the burner exceeds the boiling temperature at the operating pressure and the fuel flow is so low that heat transfer to the liquid fuel causes evaporation within the fuel channels of the burner. Liquid fuel and vapour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…With a larger gas-liquid ratio, self-pulsation occurs, which is found to determine the flow structures inside the spray cone and to generate, shed, and dissipate vortices periodically. Except for the flow rates of each propellant, scholars [23] have found that the self-pulsation can be motivated by the phase change from liquid to vapor which happens when the preheat temperature of the gas flowing through the burner exceeds the boiling temperature at the operating pressure. However, this mechanism of the self-pulsation due to the propellant phase change caused by the temperature change is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…With a larger gas-liquid ratio, self-pulsation occurs, which is found to determine the flow structures inside the spray cone and to generate, shed, and dissipate vortices periodically. Except for the flow rates of each propellant, scholars [23] have found that the self-pulsation can be motivated by the phase change from liquid to vapor which happens when the preheat temperature of the gas flowing through the burner exceeds the boiling temperature at the operating pressure. However, this mechanism of the self-pulsation due to the propellant phase change caused by the temperature change is unclear.…”
Section: Introductionmentioning
confidence: 99%